Socioeconomic Gradients in Health for White and Mexican-Origin Populations - Goldman, Noreen (© American Journal of Public Health 2006, 2006)
Objectives. We assessed whether the few findings to date suggesting weak relationships between education and health-related variables among Hispanics are indicative of a more widespread pattern. Methods. We used logistic regression models to examine education differentials (i.e., education gradients) in health behaviors and outcomes among White and Mexican-origin adults, adolescents, and infants. We gathered information from 3 data sets: the Los Angeles Family and Neighborhood Survey, the Fragile Families and Child Wellbeing Study, and the National Health Interview Survey. Results. In contrast with patterns for Whites, education was weakly associated or not associated with numerous health-related variables among the US Mexican-origin population. Among adults, Mexican immigrants were especially likely to have weaker education gradients than Whites. Conclusions. The weak relationships between education and health observed among individuals of Mexican origin may have been the result of several complex mechanisms: social gradients in health in Mexico that differ from those in the United States, selective immigration according to health and socioeconomic status, and particular patterns of integration of Mexican immigrants into US society.